2010
DOI: 10.1017/s002966511000460x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a protected mealtime policy on the energy intake and frequency of non-urgent interruptions during mealtimes at the Royal Bournemouth Hospital

Abstract: Malnutrition is both a cause and consequence of disease effecting up to 30% of patients admitted to hospital (1) and the public cost has been estimated at £13 billion a year (2) . The protected mealtime initiative (PMI), currently under the care of the national patient safety agency, aims to allow patients to eat their meals without unnecessary interruption and enable staff to assist those who are unable to eat independently (3) . Two years ago the PMI was introduced onto one ward at the Royal Bournemouth Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As patient interruptions were negatively associated with intake when all mealtime observations were analyzed, this may explain why protected mealtimes implementation was not associated with intake. Other studies have shown that interruptions can be reduced post implementation of protected mealtimes, 9,10 or remained unchanged. 7 Some components of protected mealtimes did improve after program implementation though.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As patient interruptions were negatively associated with intake when all mealtime observations were analyzed, this may explain why protected mealtimes implementation was not associated with intake. Other studies have shown that interruptions can be reduced post implementation of protected mealtimes, 9,10 or remained unchanged. 7 Some components of protected mealtimes did improve after program implementation though.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study in elderly inpatients showed no differences in energy and protein intakes after implementation of protected mealtimes and/or mealtime assistance; however, inpatients were more likely to meet daily energy requirements post implementation (pre:8% vs post: 20-31%, P o 0.01). 5 Other studies [6][7][8][9][10] have not checked whether protected mealtimes was successfully implemented, and used a variety of strategies to implement the program (such as staff inservicing, signage on wards). Thus no conclusion can be drawn from their results that show no changes in energy and protein intake.…”
Section: Introductionmentioning
confidence: 99%